Abstracts 2019
DOI: 10.1136/annrheumdis-2018-ewrr2019.85
|View full text |Cite
|
Sign up to set email alerts
|

P096 The role of the IL-23/Th17 axis as modulator of B cell-mediated (auto)immune responses

Abstract: Career situation of first and presenting authorPost-doctoral fellow.IntroductionRheumatoid arthritis (RA) is characterized by chronic synovitis and joint destruction. Autoantibodies and autoreactive B cells are a hallmark of RA. Furthermore, Th17 cells have been demonstrated to be crucial for disease development. However, checkpoints and mechanisms regulating the onset of rheumatoid arthritis (RA) remain largely unclear.ObjectivesRecently, we have demonstrated, that Th17 cells suppress the enzyme ST6 a-galacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Interleukin-12 (IL12) and interleukin-23 (IL23) have recently emerged as therapeutic targets in the treatment of autoimmune/inflammatory diseases and chronic inflammatory diseases in which the T cell dominates as the primary dysfunctional cells [1][2][3]. IL12 and IL23 are mainly produced by antigen-presenting cells like macrophages and dendritic cells, and they play a key role in naïve T-cells differentiation to Th1 and Th17 cells, respectively [4]. Their combined inhibition has demonstrated potential in the treatment of a wide range of autoimmune/inflammatory diseases [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-12 (IL12) and interleukin-23 (IL23) have recently emerged as therapeutic targets in the treatment of autoimmune/inflammatory diseases and chronic inflammatory diseases in which the T cell dominates as the primary dysfunctional cells [1][2][3]. IL12 and IL23 are mainly produced by antigen-presenting cells like macrophages and dendritic cells, and they play a key role in naïve T-cells differentiation to Th1 and Th17 cells, respectively [4]. Their combined inhibition has demonstrated potential in the treatment of a wide range of autoimmune/inflammatory diseases [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Il12b -/mice are completely protected from CIA. [46] Therefore, if this synergistic repression of Il12b occurs also under inflammatory conditions, it might be the reason for the Dx dose-sparing capacity of NAP in the treatment of this disease. On the other hand, figure 8b shows that, as expected, no statistically significant over-expression of M 2 markers is observed for either free Dx or encapsulated Dx (2.55 μм) as the concentration of Dx is higher than 100 nм which is the reported limit concentration for polarization.…”
Section: In Vitro Anti-inflammatory and Anti-angiogenic Activity Of N...mentioning
confidence: 99%
“…IL12 is decisive in regulating lineage commitment to T helper 1 cells (Th1) development, whereas IL23 is essential for the maturation and stability of IL17-producing T helper 17 cells (Th17). [46] Therefore, Dx/NAP combination and, in particular, the newly described Dx-loaded NAP bearing NPs have potential for the treatment of diseases in which IL12 and IL23 are overexpressed and Th1 and Th17 play a key role in pathogenesis. That is the case of autoimmune/inflammatory disorders like Crohn's disease, ulcerative colitis, psoriatic arthritis, rheumatoid arthritis, human multiple sclerosis, psoriasis… [51,52] This combination of FDA-approved drugs acts at a genetic level inhibiting Il12b expression levels by macrophages, a IL12-p40 subunit codifying gene, and, hence, decreasing IL12 and IL23 levels.…”
Section: In Vitro Anti-inflammatory and Anti-angiogenic Activity Of N...mentioning
confidence: 99%